2010
DOI: 10.1097/icu.0b013e32833b7a3f
|View full text |Cite
|
Sign up to set email alerts
|

Complications of strabismus surgery

Abstract: The many possible complications are rare, preventable, and treatable. Generally, surgery almost always improves, if not permanently curing, strabismic deviations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 44 publications
0
36
0
1
Order By: Relevance
“…Oculocardiac reflex (OCR), also known as Aschner phenomenon, is a subtype of vasovagal response and is one of the well-known, documented, serious complications that could occur in orbital fractures [9] and when involving surgery manipulating the extraocular muscle [10]. It can be defined as presence of dysrhythmia or a sudden heart rate decrease of more than 20% from the normal [11].…”
Section: Discussionmentioning
confidence: 99%
“…Oculocardiac reflex (OCR), also known as Aschner phenomenon, is a subtype of vasovagal response and is one of the well-known, documented, serious complications that could occur in orbital fractures [9] and when involving surgery manipulating the extraocular muscle [10]. It can be defined as presence of dysrhythmia or a sudden heart rate decrease of more than 20% from the normal [11].…”
Section: Discussionmentioning
confidence: 99%
“…This is also true of the literature. [5][6][7] However, serious complications are rare and do not occur in most patients. Patients should still be informed of these risks, but dwelling on them can increase patient anxiety before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies on strabismus surgery complications focus on serious and rare complications. [5][6][7] Few studies have reported what most patients actually experience, which are only minor side effects and inconveniences. Therefore, this study was conducted to provide objective information on patient discomfort after strabismus surgery.…”
mentioning
confidence: 99%
“…1 Both anterior segment ischemia and endophthalmitis are known complications of strabismus surgery, but are exceedingly rare. Endophthalmitis has been reported to have an incidence in the range of 1 in 30,000 to 185,000 cases, 1,2 whereas anterior segment ischemia (ASI) has a reported incidence of 1 in 13,300 cases.…”
mentioning
confidence: 99%